2019
DOI: 10.31258/jes.3.1.p.72-83
|View full text |Cite
|
Sign up to set email alerts
|

Application of Moving Class Learning Models and Teacher Pedagogical Competence on Learning Motivation and Student Learning Discipline

Abstract: This study aims to analyze the effect of the application of moving class learning models and pedagogical competencies of teachers on learning motivation and its impact on student learning discipline in SMP Negeri 2 Bandar Seikijang. The population of this research were 151 students of class VIII and IX. Sampling method used proportional random sampling using the Slovin formula, so as to obtain 110 students. Data collection used a questionnaire with a Likert scale. The data analysis technique used a path analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…There is a significant influence between learning motivation on student learning discipline (learning discipline is one indicator of affective learning outcomes). The growth of discipline in students is motivated by students' motivation to behave better, because there is a conductive environment and rewards given by the teacher (Marina et al, 2019).…”
Section: The Effect Of Student Learning Motivation On Affective Learnmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a significant influence between learning motivation on student learning discipline (learning discipline is one indicator of affective learning outcomes). The growth of discipline in students is motivated by students' motivation to behave better, because there is a conductive environment and rewards given by the teacher (Marina et al, 2019).…”
Section: The Effect Of Student Learning Motivation On Affective Learnmentioning
confidence: 99%
“…The theory of sustainable business growth is the ability of business actors to increase proactive business and business attitudes in anticipating the needs and tastes of consumers in a sustainable manner. Business owners must consider the three interrelated business growth strategies including financial growth, strategic growth and structural growth when planning business growth (Indrawati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Student learning outcomes can also be influenced by motivational factors. Oemar in Marina et al, (2019) reported that learning motivation plays a major role in the success or failure of students' activities. Goal Orientation (GO) is a form of motivation.…”
mentioning
confidence: 99%